Mechanical design of small vertical axis wind turbine - Wang Bin (КНУБА, 2018)
A new type of vertical shaft wind generator has a mechanical structure design, which can adjust the installation Angle of the wind blade according to the wind speed. When the wind force is large, the speed of the generator is higher than the rated speed. The blade Angle is adjusted by controlling the front and back movement of the electric push rod, so that the speed of the vertical shaft wind generator can be reduced to the rated speed. In this way, the stopping and fault of the wind generator caused by excessive speed can be avoided. At the same time, the braking system of the vertical shaft wind generator is designed, and the mechanical braking system is adopted.
Keywords: vertical axis wind turbine; structural design; mechanical braking; 621.311.24